2020
DOI: 10.1111/eth.13110
|View full text |Cite
|
Sign up to set email alerts
|

Odd one in: Oddity within mixed‐species shoals does not affect shoal preference by vagrant tropical damselfish in the presence or absence of a predator

Abstract: Grouping behaviour displayed by animals is usually attributed to predation and foraging-related benefits. The mechanisms of predator protection and foraging efficiency are diverse and often produce conflicting drivers of grouping behaviour. One key conflict is that between group size and phenotypic oddity. Theoretically, individuals should choose the largest available group due to multiple mechanisms associated with "safety in numbers". However, individuals should also choose the most phenotypically similar gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Apart from differential preference by the predator, mixed shoals might also provide higher vigilance (using heterospecific alarm cues) and could be an additional reason for mixed shoaling in the presence of predators ( Ward et al, 2018 ). In consensus with our findings, damselfish ( Abudefduf vaigiensis ) associate equally with conspecific shoals and shoals of the phenotypically different Australian mado ( Atypichthys strigatus ), indicating that oddity is not a universal driver of shoaling decisions ( Paijmans et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…Apart from differential preference by the predator, mixed shoals might also provide higher vigilance (using heterospecific alarm cues) and could be an additional reason for mixed shoaling in the presence of predators ( Ward et al, 2018 ). In consensus with our findings, damselfish ( Abudefduf vaigiensis ) associate equally with conspecific shoals and shoals of the phenotypically different Australian mado ( Atypichthys strigatus ), indicating that oddity is not a universal driver of shoaling decisions ( Paijmans et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…Table 6 provides examples of these claims. "These results suggest that shoal composition may not be an important driver of shoal choice in this system" Paijmans et al, 2021 "…suggesting that size is not a determinant factor for feral horse society. "…”
Section: Abstract Population Claimsmentioning
confidence: 94%
“…For example, one study found that, after accounting for group size differences, zebras in mixed-species groups under high predation risk had nearly an hour of extra foraging time, compared to zebras in single-species groups, owing to reduced investment in costly vigilance behaviours [17]. On the other hand, the 'predator confusion effect', a key mechanism by which groups neutralize predator attacks, may be less effective in mixed-species groups owing to phenotypic dissimilarity among group members [11,16,18,19]. However, this dissimilarity may provide a benefit in terms of foraging, as heterospecific group members can have partially distinct diets, reducing food competition compared to single-species groups [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%